The Problem of Aesthetic Judgement Generality in Kantian Philosophy - Žičkytė, Rūta (Problemos, 1981)
Those features of Kantian teaching on the fire and art creation which were best revealed in the works of the German philosopher and devoted to the studies of Man’s practical activities are observed in the article. The author comes to the conclusion that I. Kant was among the first ones to develop an important idea on social significance of art.